2009
DOI: 10.1590/s0100-29452009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic technology to improve oil extraction from Caryocar brasiliense camb. (Pequi) Pulp.

Abstract: ABSTRACT-The present study aims to compare yield and quality of pequi pulp oil when applying two distinct processes: in the first, pulp drying in a tray dryer at 60 o C was combined with enzymatic treatment and pressing to oil extraction; in the second, a simple process was carried out by combining sun-drying pulp and pressing. In this study, raw pequi fruits were collected in Mato Grosso State, Brazil. The fruits were autoclaved at 121ºC and stored under refrigeration. An enzymatic extract with pectinase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 9 publications
2
12
1
8
Order By: Relevance
“…Extraction processes used showed high efficiency: 54.9% for pressing without pretreatment and 66.1% for pressing with enzymatic pretreatment. These values are higher than those found by Mariano, Couri, and Freitas (2009), where different methods of extracting oil from pequi pulp were tested, including hydraulic pressing (35%) and enzymatic treatment followed by pressing (40%). Enzymatic treatment with pectinases and cellulases of goldenberry pomace followed by extraction with n-hexane enhanced oil extractability up to 7.6%, which demonstrated the efficacy of these enzymes to F I G U R E 1 Yield and efficiency (%) of pequi pulp oil extraction using cold pressing (CP) and cold pressing processes associated with enzymatic pretreatment (CPE) release the lipids from oil raw material.…”
Section: Extraction Processcontrasting
confidence: 64%
See 1 more Smart Citation
“…Extraction processes used showed high efficiency: 54.9% for pressing without pretreatment and 66.1% for pressing with enzymatic pretreatment. These values are higher than those found by Mariano, Couri, and Freitas (2009), where different methods of extracting oil from pequi pulp were tested, including hydraulic pressing (35%) and enzymatic treatment followed by pressing (40%). Enzymatic treatment with pectinases and cellulases of goldenberry pomace followed by extraction with n-hexane enhanced oil extractability up to 7.6%, which demonstrated the efficacy of these enzymes to F I G U R E 1 Yield and efficiency (%) of pequi pulp oil extraction using cold pressing (CP) and cold pressing processes associated with enzymatic pretreatment (CPE) release the lipids from oil raw material.…”
Section: Extraction Processcontrasting
confidence: 64%
“…Linolenic acid was detected only in pequi pulp oil using CP. Other authors also verified similar composition in pequi oils obtained by different extraction methods (Aquino, Borges, Queiroz, Antoniassi, & Cirillo, 2011;Mariano et al, 2009).…”
Section: Oil Compositionsupporting
confidence: 53%
“…The high presence of this species in this ecosystem, explored in an extractive way, and typical of the region, deserves special attention due to the peculiar characteristics of its fruits as flavor, color and aroma, greatly appreciated by regional population (Souza et al, 2007) for their own consumption, as well as in the commercialization of the fruit in natura (Mariano et al, 2009). The fruit of pequizeiro can be characterized as a drupe with green peel, generally containing between 1 and 4 seeds per fruit, called pyrenes, that are composed of an woody endocarp with numerous thorns, internally containing the seed or an edible almond, and enveloped by a pulp adhered to the kernel of intense yellow color, fleshy and with high oil content, called the inner mesocarp (Soares Júnior et al, 2009;Oliveira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The results show that time was the main influencing factor in the enzymatic process. This type of process for extracting oil is considered to be environmentally friendly (Mariano et al, 2009). It has also been found that particle size, water content, time, and the weight ratio of enzyme substrates affect the enzymatic process.…”
Section: Discussionmentioning
confidence: 99%